T-cell response to allergens - (:unkn) unknown (My University, 2010)
Anaphylaxis is a life-threatening IgE-dependent type 1 hypersensitivity reaction in which multiple organ systems are involved. The existence of allergen exposure and specific IgE are the major contributors to this systemic reaction. The decision of the immune system to respond to allergens is highly dependent on factors including the type and load of allergen, behavior and type of antigen-presenting cells, innate immune response stimulating substances in the same micromilieu, the tissue of exposure, interactions between T and B lymphocytes, costimulators, and genetic propensity known as atopy. Antigen-presenting cells introduce processed allergens to T-helper lymphocytes, where a decision of developing different types of T-cell immunity is given under the influence of several cytokines, chemokines, costimulatory signals and regulatory T cells. Among Th2-type cytokines, interleukin (IL)-4 and IL-13 are responsible for class switching in B cells, which results in production of allergen-specific IgE antibodies that bind to specific receptors on mast cells and basophils. After re-exposure to the sensitized allergen, this phase is followed by activation of IgE Fc receptors on mast cells and basophils resulting in biogenic mediator releases responsible for the symptoms and signs of anaphylaxis. Since the discovery of regulatory T cells, the concepts of immune regulation have substantially changed during the last decade. Peripheral T-cell tolerance is a key immunologic mechanism in healthy immune response to self antigens and non-infectious non-self antigens. Both naturally occurring CD4+CD25+ regulatory T (Treg) cells and inducible populations of allergen-specific, IL-10-secreting Treg type 1 cells inhibit allergen-specific effector cells and have been shown to play a central role in the maintenance of peripheral homeostasis and the establishment of controlled immune responses. On the other hand, Th17 cells are characterized by their IL-17 (or IL-17A), IL-17F, IL-6, tumor necrosis factor-α, and IL-22 expressions, which coordinate local tissue inflammation through upregulation of proinflammatory cytokines and chemokines. This chapter is mainly focused on antigen presentation pathways and allergen-specific T-cell responses. Copyright © 2010 S. Karger AG, Basel.